Effects of Multisystemic Therapy for Child Abuse and Neglect on severity of neglect, behavioral and emotional problems, and attachment disorder symptoms in children. (December 2020) - Buderer, Corinna; Hefti, Stephanie; Fux, Elodie; Pérez, Tania; Swenson, Cynthia Cupit; Fürstenau, Ute; Rhiner, Bruno; Schmid, Marc
Highlights: MST-CAN works well in a German-speaking area and shows good improvements in these families. MST-CAN made the environment of the family safer by reducing severity of neglect. Children showed less emotional/behavioral problems after MST-CAN and 6 months later. Children in MST-CAN may experience improvement of attachment disorder symptoms. Abstract: Children who experience child abuse and neglect are at high risk for developing emotional and behavioral problems as well as attachment disorder symptoms. Multisystemic Therapy for Child Abuse and Neglect (MST-CAN) is an evidence-based intervention for families experiencing child maltreatment. In a German-speaking environment, we aimed to investigate the effects of MST-CAN on the severity of child neglect, children's emotional and behavioral problems, and children's attachment disorder symptoms, comparing children in MST-CAN with children in residential care (comparison group). A total of 168 families entered MST-CAN between 2011 and 2017 in Switzerland. Effectiveness of the program in this group was compared with a matched comparison group (43 children). Severity of neglect showed a significant reduction after MST-CAN. Children showed significantly less emotional and behavioral problems at the end of MST-CAN and 6 months later. Children in both the MST-CAN group and comparison group showed significant improvements in emotional and behavioral total problems and attachment disorder symptoms over time. Our results showed that MST-CAN made the environment of the family safer by preventing recurrence of neglect. Thus, we conclude that MST-CAN works well in a German-speaking area.